1993
DOI: 10.2176/nmc.33.377
|View full text |Cite
|
Sign up to set email alerts
|

Intradural, Purely Extramedullary Hemangioblastoma of the Spinal Cord —Case Report—

Abstract: An unusual, purely extramedullary hemangioblastoma of the spinal cord occurred in a 59-year-old female. Myelography revealed a filling defect at the Th6 level, and computed tomographic myelography demonstrated an extramedullary intradural isodense mass at the same level. The mass was homogeneously enhanced on postcontrast computed tomographic scans. T1-weighted magnetic resonance imaging showed an isointense mass, homogeneously enhanced by contrast medium. The tumor was removed en bloc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…We found only four cases to have been reported pre- (Table 1). [12][13][14][15] The current case report is the first in which details of MRI findings are described. The key to diagnosing hemangioblastoma on MRI is to find those abnormally enlarged vessels outside the tumor mass shadow.…”
Section: Discussionmentioning
confidence: 92%
“…We found only four cases to have been reported pre- (Table 1). [12][13][14][15] The current case report is the first in which details of MRI findings are described. The key to diagnosing hemangioblastoma on MRI is to find those abnormally enlarged vessels outside the tumor mass shadow.…”
Section: Discussionmentioning
confidence: 92%
“…Haemangioblastoma is an uncommon neoplasm in humans, usually located in the cerebellum but can occur in all parts of the central nervous system . Spinal cord localisation of a haemangioblastoma is unusual; most clinical reports of the disease in humans describe intramedullary tumours, whereas intradural extramedullary growth is extremely rare . These tumours represent approximately 2–10% of all spinal cord neoplasms in people and can occur sporadically or as a part of the Von Hippel‐Lindau syndrome …”
mentioning
confidence: 99%
“…[1][2][3] Spinal cord localisation of a haemangioblastoma is unusual; most clinical reports of the disease in humans describe intramedullary tumours, whereas intradural extramedullary growth is extremely rare. 1,[4][5][6] These tumours represent approximately 2-10% of all spinal cord neoplasms in people 1,5 and can occur sporadically or as a part of the Von Hippel-Lindau syndrome. 2,3,7 In the veterinary literature, only two cases of haemangioblastoma have been reported, 8,9 both in dogs.…”
mentioning
confidence: 99%
“…Previous case reports showed that the average age of patients with extramedullary hemangioblastoma was greater than the average age of patients with all types of hemangioblastomas, with most patients in their 50's (46–66 years) [ 13 15 16 17 18 19 ]. In our study, the patients with extramedullary hemangioblastoma were 54 and 81 years old.…”
Section: Discussionmentioning
confidence: 99%